ChemInform Abstract: Cationic Palladium(II) Complexes as Catalysts for the Oxidation of Terminal Olefins to Methyl Ketones Using Hydrogen Peroxide. Issue 38 (3rd September 2015) - Cao, Qun; Bailie, David S.; Fu, Runzhong; Muldoon, Mark J.
Abstract Terminal olefins (I) are oxidized to their corresponding methyl ketones (II) using ligated Pd(II) complexes as catalyst and aqueous H2O2 as sustainable and readily available oxidant.